2022
DOI: 10.1002/jev2.12264
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from colorectal cancer cells promote metastasis via the NOD1 signalling pathway

Abstract: Pattern-recognition receptors (PRRs) have been shown to promote tumour metastasis via sensing tumour cell-derived small extracellular vesicles (EVs). Nucleotidebinding oligomerisation domain 1 (NOD1), a cytoplasmic PRR, plays a role in colorectal cancer (CRC) by detecting bacterial products. However, the precise mechanisms underlying the effects of NOD1, following identification of CRC cell-derived EVs (CRC-EVs), to potentiate CRC liver metastasis (CRC-LM), remain poorly understood. Here, we demonstrate that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 59 publications
(79 reference statements)
1
15
0
Order By: Relevance
“…G. Knockdown of stress-insensitive translocated proteins (MBD1 or TOPBP1), but not stress-sensitive proteins (ERC1, POLR2D or ST13), impairs cell viability under arsenite stress. 54,55 that can activate cytosolic signaling in recipient macrophages. TOMM20 and VDAC2 are mitochondrial proteins that can traffick between cells via nanotubes 57 .…”
Section: Main Figures Figure 1 Development Of Transitid and Character...mentioning
confidence: 99%
See 2 more Smart Citations
“…G. Knockdown of stress-insensitive translocated proteins (MBD1 or TOPBP1), but not stress-sensitive proteins (ERC1, POLR2D or ST13), impairs cell viability under arsenite stress. 54,55 that can activate cytosolic signaling in recipient macrophages. TOMM20 and VDAC2 are mitochondrial proteins that can traffick between cells via nanotubes 57 .…”
Section: Main Figures Figure 1 Development Of Transitid and Character...mentioning
confidence: 99%
“…Western blot analysis of enriched material showed that the proteins CDC42 and PTEN traffick between the tumor cytosol and macrophage cytosol ( Figure 7C-E ). Both proteins have previously been detected in cancer-derived exosomes 54, 55 , but the destination compartment within macrophages was unknown. We found that treatment of cultures with the exosome biogenesis inhibitor GW4869 reduced the transfer of both proteins to macrophage cytosol ( Figure 7E ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRC-sEVs activated macrophage nucleotide-binding oligomerization domain 1 (NOD1) signaling and promoted secretion of the pro-inflammatory cytokines IL-6 and tumor necrosis factor-α (TNF-α). NOD1-activated macrophages also promoted CRC cell metastasis [ 67 ]. Takano et al found that sEVs carrying miR-203 from CRC cells were integrated into monocytes and promoted the expression of M2 markers.…”
Section: Small Extracellular Vesicles Promote Macrophages To Undergo ...mentioning
confidence: 99%
“…However, in pathological conditions such as cancer, they can promote tumor invasion and metastasis. Recently, there has been much interest in the study of exosomes because they are carriers of molecules such as DNAs, coding and non-coding RNAs, lipids, and proteins that may have immunosuppressive effects or favor tumor invasion [6]. Among the non-coding RNAs, we have miRNAs, short RNAs of 18 to 22 nucleotides, which play a significant role in regulating gene expression at the posttranscriptional level [7].…”
Section: Introductionmentioning
confidence: 99%